2018
DOI: 10.1088/1674-1056/27/10/105205
|View full text |Cite
|
Sign up to set email alerts
|

UAV flight test of plasma slats and ailerons with microsecond dielectric barrier discharge

Abstract: Plasma flow control (PFC) is a promising active flow control method with its unique advantages including the absence of moving components, fast response, easy implementation, and stable operation. The effectiveness of plasma flow control by microsecond dielectric barrier discharge (µs-DBD), and by nanosecond dielectric barrier discharge (NS-DBD) are compared through the wind tunnel tests, showing a similar performance between µs-DBD and NS-DBD. Furthermore, the µs-DBD is implemented on an unmanned aerial vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Meanwhile, as the height increases, the efficiency of the rudder surface drops sharply. The combined control technology using aerodynamic/direct force is almost an inevitable choice for aircraft with high maneuverability [10]. The PSJA is usually mounted at the leading edge or anywhere to improve the aerodynamics around the aircraft.…”
Section: Plasma Flow Control Methodsmentioning
confidence: 99%
“…Meanwhile, as the height increases, the efficiency of the rudder surface drops sharply. The combined control technology using aerodynamic/direct force is almost an inevitable choice for aircraft with high maneuverability [10]. The PSJA is usually mounted at the leading edge or anywhere to improve the aerodynamics around the aircraft.…”
Section: Plasma Flow Control Methodsmentioning
confidence: 99%
“…During the plasma discharge the charged particles are subjected to the electric field generated by the asymmetric electrodes and collide with the neutral particles for momentum transfer, forming a directional jet from the exposed electrode to the buried electrode along the actuator surface. [4] DBD has many applications in active flow control, mainly lift increase and drag reduction, [5][6][7][8][9] noise reduction, [10,11] lateral force control [12,13] and suppression of flow separation. [14][15][16][17][18] The cited studies have demonstrated the flow control performance of DBD actuators.…”
Section: Introductionmentioning
confidence: 99%
“…Such plasma actuation is called extended DBD (EX-DBD). [13] Although a TED has the advantages of a more significant induced body force, controllable jet direction and wider plasma discharge extent than a DBD, the addition of a DC power supply will also inevitably cause an increase in power consumption. Therefore the comprehensive performance of plasma actuators still needs to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…[18] Note that the nanosecond plasma actuator has been intensively investigated as it shows great potential to control high-speed flow and is used in a wide range of flow control applications including unmanned air vehicle (UAV). [19,20] Zhang et al reported that the AC DBD plasma can generate ultrasound with frequency of approximately 100 kHz. [21] Actually, given the complexity of physics of flow separation as well as plasma discharge, some phenomena peculiar to AC-DBD-based flow control has not been reported in the literature and additional insights into the AC plasma actuation are desired.…”
Section: Introductionmentioning
confidence: 99%